THE INFLUENCE OF CAMAT LEADERSHIP ON COMMUNITY AWARENESS IN PAYING LAND AND BUILDING TAXES IN CIBEUREUM DISTRICT, SUKABUMI CITY - Erfina Juanda; Rizki Hegia Sampurna; Tuah Nur (DIA: Jurnal Administrasi Publik, 2025)
Based on the results and research discussion , it can be concluded that there is a positive and significant influence from the sub -district head's leadership on community awareness in paying land and building taxes in Cibeureum District, Sukabumi City . This is shown by the level of influence of the sub-district head's leadership on people's awareness of paying land and building taxes of 52 % . This value was obtained from the analysis results of the coefficient of determination of the regression model which was obtained as large as 0.496. This value shows that the magnitude of the influence is 52% and the remainder is influenced by other factors not explained in this study. Then, based on the correlation coefficient test , it was found that the leadership variable on community awareness in paying land and building taxes in Cibeureum District had a high level of relationship of around 0.725 , thus, the better the leadership pattern . sub - district heads implemented in Cibeureum District will increase public awareness in paying land and building taxes so that tax revenues in the District will increase.